High Plasma Concentrations of Zidovudine (AZT) Do Not Parallel Intracellular Concentrations of AZT-Triphosphates in Infants During Prevention of Mother-to-Child HIV-1 Transmission. (1st July 2016) - Kinai, Ei; Kato, Shingo; Hosokawa, Shinichi; Sadatsuki, Miyuki; Gatanaga, Hiroyuki; Kikuchi, Yoshimi; Lam, Nguyen Van; Ha, Do Quan; Kinh, Nguyen Van; Liem, Nguyen Thanh; Oka, Shinichi
Abstract : Objectives: Zidovudine (AZT) is mainly used to prevent mother-to-child HIV-1 transmission (PMTCT). Despite serious concerns on AZT-associated toxicity, there is little information on pharmacokinetics of intracellular AZT metabolites in infants. Methods: We conducted a prospective study in 31 HIV-uninfected infants who received AZT for PMTCT. Blood samples were obtained from 14 infants on postdelivery days (PDD) 1, 7, 14, and 28 and from 17 infants at 0 and 4 hours after dosing on PDD-1. Plasma AZT concentrations (pAZT) and intracellular concentrations of AZT-monophosphate (icAZT-MP), diphosphate (icAZT-DP), and triphosphate (icAZT-TP) were determined. Results: Plasma AZT and icAZT-MP concentrations were 2713 nmol/L and 79 fmol/10 6 cells in PDD-1, but decreased to 1437 nmol/L and 31 fmol/10 6 cells by PDD-28 ( P = 0.02 and P = 0.07 for all PDDs, respectively), whereas those of icAZT-DP and icAZT-TP remained low throughout the sampling period ( P = 0.29 and P = 0.61 for all PDDs, respectively) There were no differences in icAZT-TP between infants of the 2 mg/kg 4 times a day dose and 4 mg/kg twice daily dose ( P = 0.25), whereas pAZT and icAZT-MP levels were higher in the latter ( P < 0.01 and <0.01, respectively). The pAZT and icAZT-MP significantly increased from 0 to 4 hours after dosing ( P < 0.001 and <0.001, respectively), whereas icAZT-DP, icAZT-TP levels were not changed ( P = 0.41 and 0.33, respectively). Conclusions: The level of icAZT-TP did not change with age, time, or a single dose despite the wide range of pAZT concentration. A safer dosage needs to be determined because high pAZT levels do not parallel those of icAZT-TP.